Implementation Of Two-Hourly Repositioning For The Prevention Of Pressure Injury In Two Patients With Ischemic Stroke And Pneumonia In The Intensive Care Unit (ICU): A Case Study - Siti Nurina; Maria Astrid (CV. AFDIFAL MAJU BERKAH, 2026)
Pressure injury remains an important patient safety indicator and continues to pose a significant challenge in healthcare, particularly among patients with limited mobility. Patients with ischemic stroke complicated by pneumonia are at high risk of developing pressure injuries due to prolonged immobility, physical weakness, and reduced activity tolerance. In the ICU of Hospital X, five cases of pressure injury were reported between January and December 2025. Furthermore, from January to May 2026, a total of 146 bedridden patients were identified as being at risk for pressure injury based on the COMHON Index. Repositioning every two hours is a recommended nursing intervention for preventing pressure injuries. To analyze the implementation of nursing care through two-hourly repositioning as an intervention to prevent the risk of pressure injury in two patients with ischemic stroke and pneumonia. This study employed a case study design using the nursing care process involving two patients with ischemic stroke complicated by pneumonia who were at risk of developing pressure injury. Patient assessment was conducted using the COMHON Index, followed by the implementation of two-hourly repositioning and regular skin condition monitoring throughout the course of care. Two-hourly repositioning was successfully implemented according to the planned nursing interventions. During the two-day observation period, neither patient developed a pressure injury, and skin integrity was maintained. In the patient classified as high risk, blanchable erythema was observed over the sacral area but improved following regular repositioning and continuous skin assessment. Two-hourly repositioning is an effective nursing intervention that supports the prevention of pressure injury in patients with ischemic stroke and pneumonia. This intervention should be implemented consistently and accompanied by regular skin assessment to maintain skin integrity.